Identification of an ATP-binding cassette transporter involved in bicarbonate uptake in the cyanobacterium Synechococcus sp. strain PCC 7942 - Omata, Tatsuo (The National Academy of Sciences, 1999)
Exposure of cells of cyanobacteria (blue–green algae) grown under high-CO(2) conditions to inorganic C-limitation induces transcription of particular genes and expression of high-affinity CO(2) and HCO(3)(−) transport systems. Among the low-CO(2)-inducible transcription units of Synechococcus sp. strain PCC 7942 is the cmpABCD operon, encoding an ATP-binding cassette transporter similar to the nitrate/nitrite transporter of the same cyanobacterium. A nitrogen-regulated promoter was used to selectively induce expression of the cmpABCD genes by growth of transgenic cells on nitrate under high CO(2) conditions. Measurements of the initial rate of HCO(3)(−) uptake after onset of light, and of the steady-state rate of HCO(3)(−) uptake in the light, showed that the controlled induction of the cmp genes resulted in selective expression of high-affinity HCO(3)(−) transport activity. The forced expression of cmpABCD did not significantly increase the CO(2) uptake capabilities of the cells. These findings demonstrated that the cmpABCD genes encode a high-affinity HCO(3)(−) transporter. A deletion mutant of cmpAB (M42) retained low CO(2)-inducible activity of HCO(3)(−) transport, indicating the occurrence of HCO(3)(−) transporter(s) distinct from the one encoded by cmpABCD. HCO(3)(−) uptake by low-CO(2)-induced M42 cells showed lower affinity for external HCO(3)(−) than for wild-type cells under the same conditions, showing that the HCO(3)(−) transporter encoded by cmpABCD has the highest affinity for HCO(3)(−) among the HCO(3)(−) transporters present in the cyanobacterium. This appears to be the first unambiguous identification and description of a primary active HCO(3)(−) transporter.